Legal and Accounting Considerations for Non-Profit Organizations: A Comparative Study of Macedonian and Croatian Regulations - Dionisijev, Ivan; Perica, Ivana (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
Non-profit organizations play a critical role in addressing societal needs and fostering social welfare. They depend on robust accounting frameworks to ensure transparency, accountability, and effective financial management. However, the legal and regulatory environments governing NPO accounting practices vary internationally, impacting operational and reporting requirements. In recent years, North Macedonia and Croatia have witnessed substantial growth in their non-profit sectors, spanning education, healthcare, environment, and social development. With an increasing number and complexity of NPOs, it is essential to analyze the legal frameworks shaping their accounting practices to ensure reliable and comparable financial data. This study conducts a comparative analysis of the legal frameworks and accounting regulations governing NPOs in North Macedonia and Croatia. It examines aspects such as registration procedures, tax regulations, financial reporting, and governance requirements. The comparative analysis in this research paper provides insights into the intricacies of legal, taxation, and accounting aspects within NPOs in North Macedonia and Croatia. It underscores the need for NPOs to navigate specific regulations governing their operations in each country. Researchers, policymakers, and practitioners can draw valuable insights from this study to gain a deeper understanding of challenges and opportunities within the non-profit sector in these contexts. Significant potential exists for future comprehensive analysis utilizing a quantitative methodology coupled with a meticulously crafted questionnaire. This survey instrument could be systematically distributed to a purposive sample of NPOs in both countries under investigation. Furthermore, interviews with duly authorized representatives of NPOs, strategically scheduled in the research timeline, hold promise for enriching our comprehension of the responses garnered through the administered questionnaires.
Keywords: Non-profit organizations; accounting; North Macedonia; Croatia